The "mass of people" in the postmodern perspective according to Jose Ortega-i-Gasset's "Mass Rebellion" - Chaghalidze, Eka (Procedia of Social Sciences and Humanities, 2022)
The article "Mass Revolt in the Postmodern Perspective by Jose Ortega-i-Gasset" deals with Jose Ortega-i Gasset and Martin Heidegger's definition of the specifics of mass society. Their views on "mass society", "mass man" and "man - mass". The main focus is on the nature of mass society in the post-righteous era, as well as on the new features of the postmodern era of the "human mass". The concluding section summarizes and outlines the role of mass culture in the postmodern era, how the relationship between man-mass and the intellectual in the postmodern era can be imagined.